Glycerol as alternative substrate for bioethanol production using free and immobilized Escherichia coli SS1 - Adnan, Nur Amelia Azreen (2014)
Increase in the crude oil price and the concern about climatic change has resulted in the rapid increase of biodiesel production. In the production of this biofuel, glycerol will essentially generate as by-product. As a result, the production of glycerol has also increased. Biofuel from glycerol can be categorized as second generation of biofuels where it can be used to replace the first generation of biofuel including glucose and vegetable oils as feedstock to reduce the competition between biofuel and food production. Thus the aim of this study is to carry out bioethanol production using glycerol in batch and continuous fermentation by free and immobilized Escherichia coli SS1. Bioethanol production was carried out using both free and immobilized cells in 2 liter bioreactor with 800 mL working volume. Glycerol concentration of 20 g/L, 35 g/L and 45 g/L were used as initial substrate concentration in batch free cells fermentations. Dilution rate of 0.1/h and 0.2/h were used and was selected based on the maximum specific growth rate from batch fermentation. Immobilization of E.coli SS1 was done by using sodium alginate and calcium chloride as crossed link agent. Optimization study was done to determine the stability and rigidity of alginate beads. Parameters involved in this optimization study were sodium alginate concentration, calcium chloride concentration, beads diameter and initial pH of medium. The optimum conditions for cell immobilization were 0.2 M calcium chloride, at pH 7 with 3% concentration of sodium alginate and beads diameter of 3 mm. Results showed that high glycerol concentration did not affect the yield of ethanol with the yield was closed to theoretical yield; 1 mol ethanol per 1 mol glycerol. Dilution rate of 0.1/h was the optimum dilution rate to be used in this fermentation where glycerol consumption and ethanol production was similar to batch fermentation by yielding 1 mol ethanol per mol glycerol. Continuous fermentation of immobilized E. coli SS1 was done by using the optimized beads with the dilution rate of 0.2/h and 20 g/L. The results showed that immobilized cells can last up to 3rd cycle of continuous fermentation. Ethanol production obtained was 6.17 g/L by utilizing approximately 19 g/L glycerol. The yield achieved was 0.65 mol ethanol per mol glycerol. Compare with other studies, the result in this experiment was slightly lower where other managed to obtain about 0.6 to 0.8 mol ethanol per mol glycerol, respectively.